A case report of obstructed spigelian hernia - Naser, Jamal Abdul; Jahan, Shamima; Sikder, Alamgir Hossain; Masud, Shahidul Islam; Hossain, Md Afzal; Rahman, Molla Mizanur (Journal of Dhaka National Medical College & Hospital, 2023)
Abdominal wall hernias through the arcuate line termed spigelian hernias are rare. they constitute approximately 1% (range 0.1-2%) of all hernia. Developing via the spigelian fascia, thus called lateral, these types of hernia tend to go undetected and peak at about 50-60 years old. We present a case report of 63 years old Muslim female presented with history of gradually increasing lump and vague abdominal pain at right lower abdomen for past 6 months. On examination we found that a soft ill-defined swelling was palpable in the right illiac fossa slightly above and lateral to the deep inguinal ring without expansile cough impulse. CT scan in prone position was done and it finally revealed the defect adjacent to the semilunar line and at the lateral edge of the rectus muscle. There was a 3 cm defect lateral and superior to the deep ring under the external oblique aponeurosis and defect was sutured with 2-0 poly propylene by interrupted sutures. A 15 x 15 cm poly propylene mesh was placed over the defect under external oblique aponeurosis J. Dhaka National Med. Coll. Hos. 2023; 29 (02): 54-57